A review of the blood transfusion practices in neuroanesthesia in the perioperative period in a tertiary care hospital - Ali, Zulfiqar; Hassan, Nelofar; Mehdi, Saqib; Shah, Mubashir A.; Bijli, Akram Hussain; Khan, Talib (International Journal of Research in Medical Sciences, 2017)
Background: Blood transfusion involves the administration of blood and blood components. Neurosurgical procedures are associated with significant blood loss with the need for blood transfusion in the preoperative, intraoperative and postoperative period to maintain optimal hemodynamic and cerebral oxygenation. Various neurosurgical procedures as traumatic brain injury, complex spinal surgeries, and endovascular neurosurgical procedures may need blood transfusions to maintain the optimal physiology. Methods: This study was performed prospectively at a tertiary care hospital in northern India with about a work load of 800 to 1000 elective neurosurgical surgical procedures being done per year. This data was collected prospectively over a period of one year from the patients being operated for elective neurosurgical procedures and later on shifted to the neurosurgical intensive care unit and the neurosurgical wards. The patients operated for emergency procedures for traumatic brain surgery were not included in the study. Results: A total of 455 elective neurosurgical procedures were done during the study period. Out of these 455 patients there were 95 patients who were in the paediatric age group with age less than 12 years. Out of 360 adult patients 85 patients were in need of blood transfusion which constituted 23.6 percent of the operated patients. Out of these 85 patients 45 patients needed two transfusions in the form of whole blood or packed cells, 40 patients needed a single transfusion.42 units of fresh frozen plasma were transfused to 17 patients with 15 patients receiving platelet transfusions. Conclusions: In conclusion, neurosurgical population is associated with significant blood loss and a requirement of blood transfusion. About 47 percent of paediatric population needed blood transfusion in our study with around 24 percent of adult population. The transfusion requirement was mainly seen in patients with craniostenosis, meningiomas, cerebello pontine tumours and meningiomas.